2005
DOI: 10.1242/jcs.01577
|View full text |Cite
|
Sign up to set email alerts
|

Multiple rows of cells behind an epithelial wound edge extend cryptic lamellipodia to collectively drive cell-sheet movement

Abstract: The mechanism by which epithelial, endothelial and other strongly cell-cell adhesive cells migrate collectively as continuous sheets is not clear, even though this process is crucial for embryonic development and tissue repair in virtually all multicellular animals. Wound closure in Madin-Darby canine kidney (MDCK) epithelial cell monolayers involves Rac GTPase-dependent migration of cells both at and behind the wound edge. We report here for the first time that cells behind the margin of wounded MDCK cell mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
379
4
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(410 citation statements)
references
References 74 publications
26
379
4
1
Order By: Relevance
“…The active implication of the cells several rows behind the border has been identified in the MDCK system (9,20). Indeed, these references report cells that move actively within the epithelium, in a fibroblast way, by using a so-called ''cryptic'' lamellipodium that finds its way under the other cells of the monolayer.…”
Section: Migration Triggered By a Model Wound And Advantages Of The Amentioning
confidence: 99%
See 1 more Smart Citation
“…The active implication of the cells several rows behind the border has been identified in the MDCK system (9,20). Indeed, these references report cells that move actively within the epithelium, in a fibroblast way, by using a so-called ''cryptic'' lamellipodium that finds its way under the other cells of the monolayer.…”
Section: Migration Triggered By a Model Wound And Advantages Of The Amentioning
confidence: 99%
“…This migration is associated with small GTPases of the Rho family whose activation is not restricted to the border cells but extends as far as 4-10 cell rows within the epithelium (20). At the same time, as already mentioned, the epithelia keep their integrity; the cell-cell contacts are maintained in particular by cadherins (21), although it has been observed that MDCK cells migrate actively within the monolayer by developing active ''cryptic'' lamellipodia under the other cells (20). Interestingly, although the onset of migration significantly depends on the initial cell density (22), cell division does not play an active role but rather appears to redensify the monolayer (20).…”
mentioning
confidence: 99%
“…1), which are critically involved in cell growth and differentiation and morphogenesis (13,38,52,110,111). Because the airway epithelium is continuously subjected to injury due to environmental stress, it possesses an exceptional capacity to repair itself (112,113), through a coordinated response involving rapid spreading and migration of neighboring cells, cell proliferation and redifferentiation, to restore the original mucociliary epithelium (103,114,115). Using in vitro wound models in cultured airway epithelial systems, DUOX1 was found to play a critical role in cell migration as part of the wound repair response (87,108), illustrating an additional function of DUOX1 in maintenance of epithelial integrity.…”
Section: Functions Of Epithelial Duox: Host Defense and Intracellularmentioning
confidence: 99%
“…The central scratch has been used with multiple cell types and, as the monolayers heal the wound in a characteristic manner, they have been used to study cell polarization, matrix remodeling, cell migration, and numerous other processes [12]. Kornyei et al (2000) [14] used an in vitro scratch-wound model to investigate astroglial responses to mechanical injury while Saga et al (2003) [15], Liang et al (2004) [16], Farooqui et al (2004) [17], and Walker et al (2004) [18] used the cell scratch-wound model to study the proliferative and migratory responses of different cells. Lau et al (2001) [19] focused on the production of four inflammatory cytokines in primary culture using an injury model which simulated in vivo mechanical trauma and reported that all four cytokines began to increase 1 hour post-scratch and remained at high levels throughout the experiment [19].…”
Section: Introductionmentioning
confidence: 99%